Microscopic decompressive laminectomy versus percutaneous endoscopic decompressive laminectomy in patients with lumbar spinal stenosis: protocol for a systematic review and meta-analysis - Hua Zhang; Rong Wang; Guodong Gao; Xiuxia Li; Xiaogang Zhang; Daping Qin; Guodong Yang (BMJ Open)
Introduction Lumbar spinal stenosis (LSS) is a common lumbar degenerative disease in the elderly, usually requiring surgery if conservative treatment fails. Microscopic decompressive laminectomy (MDL) and percutaneous endoscopic decompressive laminectomy (PEDL) have been widely used to treat LSS. This study aims to provide a protocol for the evaluation and comparison of the efficacy, safety and applicability between MDL and PEDL.Methods and analysis We will search for randomised controlled trials (RCTs) comparing MDL and PEDL for treating LSS from inception to December 2019 in the following databases: PubMed, The Cochrane Library, Web of Science, Embase and China Biology Medicine. The quality of included studies will be assessed using the risk of bias tool recommended by the Cochrane Handbook 5.2.0. Subsequently, a meta-analysis will be performed using RevMan 5.3 software.Ethics and dissemination Given the nature of this study, no ethical approval will be required. The protocol will be disseminated via a peer-reviewed journal.PROSPERO registration number CRD42020164765.